An outbreak of neonatal gastroenteritis due to E. Coli - Muzief Munir; Tjandra Husada; I. Mustadjab; J. W. A. Supit (Indonesian Pediatric Society, 1981)
An outbreak of E. coli diarrhea in the neonatal ward of the Pediatric Department, Gunung Wenang General Hospital Manado. Indonesia has been reported. Factors influencing the easy and rapid spreading of infection have also been forwarded.The outbreak was apparently initiated by a patient admitted to the hospital which then involved 33 infants. Positive stool cultures of 16 infants revealed E.coli 055: K 59 (B) and 0126: K 71 (B) H2.Oral Kanamycin and Tetracycline gave satisfactory results. Controlling measures carried out succeeded in preventing more widespread 0/ the outbreak. Due to ever-changing resistance of E. coli to antibiotics identification of the causative agent followed by a sensitivity test remains the key to successful treatment.